The effect of the use of thyme honey in minimizing radiation - induced oral mucositis in head and neck cancer patients: a randomized controlled trial - Charalambous, Melanie; Raftopoulos, Vasilios; Paikousis, Lefkios; Katodritis, Nicos; Lambrinou, Ekaterini; Vomvas, Dimitrios; Georgiou, Morpho; Charalambous, Andreas (My University, 2018)
Purpose: Radiation-induced oral mucositis is one of the main side effects during and after the treatment of head and neck cancer patients. The study was designed to provide evidence on the effectiveness of thyme honey on oral mucositis management. Methods: This was a randomised controlled trial (RCT) with 72 head and neck cancer patients who were divided either to the intervention group (thyme honey rinses) or to the control group (saline rinses). Oral mucositis was assessed according to the Radiation Therapy Oncology Group (RTOC criteria), and assessments were performed weekly starting at the 4th week of the radiotherapy for seven weeks and repeated once 6 months later. Additionally, the Oral Mucositis Weekly Questionnaire (OMWQ) was given at 4th week of radiotherapy, 1 month after the completion of radiotherapy and 6 months later. The ClinicalTrials.gov Identifier for this study is NCT01465308. This paper reports on the findings regarding thyme honey's effectiveness on oral mucositis. Results: Generalized estimating equations revealed that patients in the intervention group were graded lower in the objective assessment of oral mucositis (p < 0,001), maintained their body weight (p < 0,001) and showed an improvement in their global health (p = 0.001) compared to the control group. Quality of life of the patients in the same group was also statistically significantly higher than that of the patients of the control group (p < 0,001). Conclusion: The study provided evidence on the positive effect of thyme honey on the management of radiation-induced oral mucositis and quality of life in head and neck cancer patients.
Keywords: Head and neck cancer; Honey; Management; Radiation-induced mucositis